Fundamental bases for the improving action of novel enzyme-oxidant combinations in frozen dough - Oshikiri, Reona (Kansas State University, 2013)
The market for frozen goods is expanding and the frozen dough goods sector still has potential to expand its market. It is well known that deterioration in bread quality occurs during frozen dough/bread production. In addition, it is known that dough rheology influences bread quality. To prevent deterioration of bread quality, many additives have been used and researched. Combinations of oxidants (potassium bromate and ascorbic acid) are widely used worldwide. However, potassium bromate may be carcinogenic to humans, and it has been detected in bread after baking. Since it has been prohibited or strictly limited in many countries, many researchers have tried to find a replacement. Ascorbic acid is safe for human intake, and does not persist in bread. However, it is not as effective as potassium bromate. Possible replacements in frozen doughs include oxidant (ascorbic acid)-enzyme combinations. This study evaluated the effects of ascorbic acid-specific enzyme combinations as a replacement for the potassium bromate in frozen dough and related the effects to dough behavior (gluten network strength) as evaluated by dynamic oscillation rheometry. Bread quality was evaluated by test baking. Based on the results from fresh baking studies, potassium bromate can be replaced by an optimum level combination of ascorbic acid and hemicellulase/endo-xylanase. This combination clearly improved loaf volume, and crumb grain over both control and potassium bromate containing doughs. For frozen dough/bread production, the addition of all additives improved bread quality, but ascorbic acid and endo-xylanase containing dough resulted in higher volume, and better crumb structure than did dough containing potassium bromate. Dough rheology experiments show that rheology was affected by both the process and additives. Strain sweeps gave the information about dough stability. Both the additives and proofing improved dough stability. Dough behavior (gluten network strength) was assessed by frequency sweeps. Dough containing ascorbic acid and endoxylanase was most stable during frozen dough processing.
Keywords: Frozen dough; Bread; Enzyme; Dough rheology; Rheometer; Agriculture, General (0473)